URGENSI KAIDAH AL URF DALAM MENERAPKAN HUKUM SYARA - Ade Fariz Fahrullah (Al-Bayyinah, 2018)
Habit can influence legal material, proportionally. Islamic law does not position adat as a nonimplicative external factor, but on the contrary, provides accommodation space for adat. This fact, among others, causes Islamic law to be flexible. The character of Islamic law that is accommodative of adat (tradition) is very much in line with the function of Islam as a universal religion (for the whole world). "Face" of Islam in various peoples of the world does not have to be the same (monolithic). The need to reconsider the position of Al-Adat and Al Urf in the structure of Islamic law building. The thinking of Islamic law, both in the form of fatwas, court decisions, laws made for Muslim societies and the laws contained in the books of fiqh, there are more or less elements of Al-adah. The position of Al urf in the building of Islamic law is a material for establishing Islamic law.